The long-term effect of comprehensive geriatric care on gait after hip fracture: the Trondheim Hip Fracture Trial—a randomised controlled trial. Issue 3 (March 2016) - Thingstad, P.; Taraldsen, K.; Saltvedt, I.; Sletvold, O.; Vereijken, B.; Lamb, S.; Helbostad, J.
Abstract Summary At present, most hip fracture patients are treated in orthopaedic wards. This study showed that a relatively short hospital intervention based on principles of comprehensive geriatric assessment resulted in safer and more efficient gait as long as 1 year following the fracture as compared to conventional orthopaedic treatment. Introduction Hip fracture patients are frail, and the fracture is usually followed by substantial decline in gait function. Few studies have assessed gait characteristics other than gait speed and knowledge about the effect of early intervention on long-term gait outcome is sparse. The purpose of this study was to evaluate the long-term effect of pre- and post-surgery Comprehensive Geriatric Care (CGC) on ability to walk, self-reported mobility and gait characteristics in hip fracture patients. Methods Two armed, parallel group randomised controlled trial comparing CGC to conventional Orthopaedic Care (OC) in pre- and early post-surgery phase. Hip fracture patients (n = 397), community-dwelling, age >70 years and able to walk at time of the fracture were included. Spatial and temporal gait characteristics were collected using an instrumented walkway (GAITRite® system) 4 and 12 months post-surgery. Results Participants who received CGC had significantly higher gait speed, less asymmetry, better gait control and more efficient gait patterns, more participants were able to walk and participants reported better mobility 4 and 12 months following the fracture as compared to participants receiving OC. Conclusions Pre- and post-surgery CGC showed an effect on gait as long as 1 year after hip fracture. These findings underscore the importance of targeting the vulnerability of these patients at an early stage to prevent gait decline in the long run. As presently, most hip fracture patients are treated in orthopaedic wards with larger focus on the fracture than on frailty, these results are important to inform new models for hip fracture care.